PENGHAMBATAN SERANGAN Sclerotium rolfsii PENYEBAB REBAH KECAMBAH PADA KEDELAI DENGAN BAKTERI KITINOLITIK - Novi Malinda; Dwi Suryanto; Kiki Nurtjahja (Saintia Biologi, 2012)
The inhibition of Sclerotium rolfsii as causal agent of soybean damping off by using chitinolytic bacteria were studied in Laboratory of Observation Pest and Disease UPT-BPTPH 1 and Laboratory of Microbiology, Department of Biology, Faculty of Mathematics and Natural Sciences, University of Sumatera Utara, Medan. The aim of this research was to investigate the ability of chitinolytic bacteria to inhibit the growth of S. rolfsii. Six isolates of chitinolytic bacteria were used in this study. The inhibition zone between colony of the bacteria and the fungus was measured. The result showed that the bacterial isolates has different ability in inhibiting the growth of S. rolfsii. Enterobacter sp. BK15 and Bacillus sp. BK13 were the most effective in inhibiting the growth of S. rolfsii with inhibition zone of 3.70 cm and 3.75 cm, respectively. The less effective was shown by Enterobacter sp. PB17 with inhibition zone of 0.10 cm, while Enterobacter cloacae LK08 have no ability to inhibit S. rolfsii. The seeds soaked in bacterial suspension by Bacillus sp. BK13 dan Enterobacter sp. BK15 were able to reduce damping off by 44.4% and 50%, respectively. Keywords: Bacillus sp., damping off, Enterobacter sp., Sclerotium rolfsii, soybean